The Transatlantic Migration of Ideas: Florian Znaniecki in America in the Years 1914–1919 - Dominiak, Łukasz (Stan Rzeczy, 2018)
This text critiques a classic sociological text, The Polish Peasant in Europe and America. The value of the work, which consists in the successful combination of elements from several intellectual traditions, is presented in connection with the biographical and historical background of one of the authors, Florian Znaniecki. In conclusion, the author makes a number of remarks concerning the special situation of migrants in global intellectual networks.